A resolution based description logic calculus - Zombori Zsolt; Symposium of Young Scientists on Intelligent Systems (3.) (2008) (Budapest) (2010)
We present a resolution based reasoning algorithm called DL calculus that decides concept satisfiability for the SHQ language. Unlike existing resolution based approaches, the DL calculus is defined directly on DL expressions. We argue that working on this high level of abstraction provides an easier to grasp algorithm with less intermediary transformation steps and increased efficiency. We give a proof of the completeness of our algorithm that relies solely on th e ALCHQ tableau method without requiring any further background knowledge.
Keywords: Természettudományok; Számítás- és információtudomány